Gestão de resíduos sólidos em instituições federais: o caso da UFERSA Campus Angicos - Santos, Juliana Estefanie da Silva (Universidade Federal Rural do Semi-Árido, 2019)
This article presents a discussion about the problem between the adequacy of the norms of solid waste before Federal Law 12.305/2010 and the federal public institutions. This study provides information on the current solid waste management situation of the Federal Rural Semi-Arid University in the Angicos-RN Campus and the way in which it is seeking to adapt and meet the national policy in question. The objectives are to identify which waste is produced; describe the destination processes; and to verify the difficulties of the management, relating to the legislation, about solid urban waste. The methodology of the work was based on the collection of bibliographic data and interviews with those responsible for waste management at UFERSA. Regarding the ends, the research is characterized by being exploratory and the means, characterized by being bibliographic and a case study. The results show that the university has been seeking more visible actions to raise awareness among the academic community, which is in line with environmental management in the institution, but still has great difficulties for the adequacy of legislation, especially on the destination of the collection.
Artigo Acadêmico
Keywords: Gerenciamento dos resíduos; Política nacional de resíduos sólidos; Universidade; Gestão ambiental; Solid waste management; National policy on solid waste; University; Environmental management; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA